Stereo animated pictorial space : Le Phénomène Atmosphérique - Conradi, Ina (2021)
How can artists influence new technological initiatives and push the expressive capabilities of animation and 3D stereoscopy towards a new pictorial space? How can we create fully immersive paintings where large scale moving paint marks and textures would appear to exist in real space? Written at the starting point of this research, this paper will try to describe it, with emphasis on the first art works produced.